A Comparative Study of Immunohistochemical, Hematoxylin and Eosin, and Giemsa Stains for Demonstration of Helicobacter pylori in Cases of Chronic Antral Gastritis - Neeti Goyal; V. Srinivas; Arun Gupta; Jasvinder Kaur Bhatia; Pragya Sharma; Prabha Shankar Mishra; Naveen Chawla; Umesh Kapoor (Journal of Marine Medical Society)
Background: Chronic gastritis is a common gastrointestinal problem all over the world. It is most frequently associated with Helicobacter pylori (H. pylori). These Gram-negative bacilli can be detected by different methods, both invasive and noninvasive techniques. It has been found in studies that there is no single gold standard stain, for detection of H. pylori, on endoscopic biopsies which is universally applicable to all laboratories. Materials and Methods: This was a prospective study carried out in the department of pathology of a tertiary care hospital. One hundred patients of chronic antral gastritis using simple random sampling irrespective of age and sex diagnosed clinically formed the study population. Comparison among three different stains, i.e., hematoxylin and eosin (H and E), Giemsa, and immunohistochemistry (IHC), on all endoscopic gastric biopsies was carried out. Results: Of the three methods compared for detection of H. pylori, the maximum sensitivity to detect H. pylori was seen by IHC ie 98.25%, while Giemsa stain showed sensitivity of 94.92 % and H and E stain showed a sensitivity off 83.58%. While we observed a specificity and positive predictive value of around 78.78% & 88.89% respectively for H and E, specificity and positive predictive value of around 58.54% & 76.7% respectively for Giemsa and specificity and positive predictive value of around 51.2% & 66.67%respectively for IHC.Hence on comparative analysis though sensitivity with IHC is more, however specificity and positive predictive value to detect Hpylori is the lowest of all three. Conclusion: We conclude that even though many stains including IHC can detect H. pylori, the simplest and cheapest way of detection is by conventional stain, i.e., H and E stain, which is sufficient for detection of H. pylori in the diagnosis of chronic gastritis.